A Comparative Study between Digital Transactions and Cash Transactions: An Analytical Study - Biswojit Swain, Abhishek Kumar, Sudhanshu Sekhar Dhir , Kumar Devadutta , Tapas Ranjan Dash (International Journal of Advanced Science and Technology, 2020)
Long years ago, transactions were made by the help of Barter system, where goods and services were exchanged by goods and services. Later on with the introduction of coins and notes, goods and services were exchanged with coins and notes. But after sometime there was the evolution of digital payment system. Both cash transactions and digital transactions have their pros and cons. After demonetization on November 8th, 2016, India saw an increased use of different internet payment systems for money transfer through various devices. NPCI (National Payments Corporation India) launched Bharat interface for Money (BHIM) an application run on UPI (Unified Payment Interface) in December 2016 to cater the growing online payment needs. The different modes of digital payments saw a drastic change in usage in the last 4 years. Digital transactions include transactions through credit cards, debit cards and other digital wallet platform. In this paper 217 sample has been collected and it was found that there is no significant difference of age with respect to digital transactions and cash transactions. But there is significant difference of gender, income group and education with respect to digital transactions and cash transactions.